Late recovery of phrenic nerve palsy in a neonate: A case report - Bagaria, Anjali; Batra, Prerna; Harit, Deepika; Bhatt, Shuchi (Indian Journal of Child Health, 2019)
Hyperextension of the neck at birth can injure the phrenic nerve and/or brachial plexus usually at the point where the phrenic nerve crosses the brachial plexus. We present a case of the preterm baby, who had Erb’s palsy and diaphragmatic paralysis since birth after breech delivery. Persistent respiratory distress and chest X-ray gave a clue to diagnosis, which was confirmed on ultrasound. The baby recovered on the conservative approach at 2 months of life without surgical plication. This study describes that late spontaneous recovery up to 2 months is possible in a newborn with respiratory distress due to phrenic nerve palsy.